Tectonic rotations in central Chile: New insights on the southern limit of the Maipo Orocline - Puigdomenech Negre, Carla Gimena (2020)
The Maipo Transition Zone or Maipo Orocline represents a change in strike of the topography from N–S between 30° and 33°S to an NNE-SSW trend to the south. The southern flank of the Maipo Orocline can be traced along strike to around 38°S. There the Andean margin exposes another orogen bending, the Arauco Orocline. Although the tectonic evolution of this segment of the Andean chain is relatively well constrained, the limit between both oroclines is unclear. In this paper, we show the results of a paleomagnetic study carried out in three plutons of Upper Triassic age located along the Coastal Cordillera of central Chile between 35° and 37°S. Paleomagnetic analysis from Constitución Granite and Cobquecura Pluton shows an increase of clockwise vertical-axis rotations from north to south consistent with previous data, whereas results obtained in the Hualpén Stock, located to the south, shows minors counter-clockwise rotations. This change in the rotation pattern would reflect the Maipo and Arauco Oroclines limit. The similar amounts of tectonic rotations recorded by Mesozoic and Miocene rocks indicate that the whole area behaved as a single block and constrains the maximum possible age for the occurrence of tectonic rotations to Miocene.